2017
DOI: 10.1074/jbc.m117.779371
|View full text |Cite
|
Sign up to set email alerts
|

The Mcm2–7-interacting domain of human mini-chromosome maintenance 10 (Mcm10) protein is important for stable chromatin association and origin firing

Abstract: The protein mini-chromosome maintenance 10 (Mcm10) was originally identified as an essential yeast protein in the maintenance of mini-chromosome plasmids. Subsequently, Mcm10 has been shown to be required for both initiation and elongation during chromosomal DNA replication. However, it is not fully understood how the multiple functions of Mcm10 are coordinated or how Mcm10 interacts with other factors at replication forks. Here, we identified and characterized the Mcm2-7-interacting domain in human Mcm10. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 73 publications
(104 reference statements)
0
18
0
1
Order By: Relevance
“…We observed that human MCM10 mainly binds to MCM4, 6 and 7 (unpublished results), which may directly bind to single-stranded DNA during DNA unwinding, and we also showed that MCM10 binds to the ATP-binding domain of MCM6 (Hosoi et al, 2016). A recent study showed that MCM10 activity to stimulate DNA replication in human cells requires its two MCM2-7-interacting domains, located in the central domain (amino acids 200 -482) and carboxyl-terminal region (amino acids 530 -655) (Izumi et al, 2017). It was also suggested that an interaction of Mcm10 and double-hexameric Mcm2-7 is required for helicase splitting and activation during S phase (Quan et al, 2015).…”
Section: Muta�onmentioning
confidence: 99%
“…We observed that human MCM10 mainly binds to MCM4, 6 and 7 (unpublished results), which may directly bind to single-stranded DNA during DNA unwinding, and we also showed that MCM10 binds to the ATP-binding domain of MCM6 (Hosoi et al, 2016). A recent study showed that MCM10 activity to stimulate DNA replication in human cells requires its two MCM2-7-interacting domains, located in the central domain (amino acids 200 -482) and carboxyl-terminal region (amino acids 530 -655) (Izumi et al, 2017). It was also suggested that an interaction of Mcm10 and double-hexameric Mcm2-7 is required for helicase splitting and activation during S phase (Quan et al, 2015).…”
Section: Muta�onmentioning
confidence: 99%
“…The region encompassing amino acids 530-655, also known as the MCM2-7 interaction region, was mapped as a determinant domain of MCM10 degradation under induction by Vpr [20,43]. Previously, little was known about the 530-633 region of MCM10, identified as a newly identified functional domain, flanked by an ID and involved in parts of CTD.…”
Section: Discussionmentioning
confidence: 99%
“…While quantitative measurement of protein levels did not identify differences in expression of full-length protein between the patient and healthy donors, the cell-cycle dependent changes in expression of MCM10 also make it difficult to draw quantitative conclusions based on this measurement. With relative expression of MCM10 highest in S phase (28), it is likely that cell cycle-dependent protein regulation affects the overall expression of MCM10 in patient cells, which we have shown are more frequently detected in S phase than healthy donor control cells.…”
Section: R a F Tmentioning
confidence: 83%
“…Furthermore, direct interaction of di-ubiquitinated MCM10 with PCNA is required for DNA elongation (42). Human MCM10 interacts directly with the CMG helicase through MCM2 and CDC45, supporting chromatin association of MCM10 and efficient firing and elongation during replication (28,30). To further probe the effect of the R426C mutation on replisome formation, we immunoprecipitated WT MCM10 or MCM10 R426C using turboGFP and probed for POLA and MCM2, CDC45 and PCNA.…”
Section: Mutations In Mcm10 Affect Protein Localization and Functionmentioning
confidence: 99%
See 1 more Smart Citation